2019
DOI: 10.1101/679316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying epigenetic biomarkers of established prognostic factors and survival in a clinical cohort of individuals with oropharyngeal cancer

Abstract: Smoking status, alcohol consumption and HPV infection (acquired through sexual activity) are the predominant risk factors for oropharyngeal cancer and are thought to alter the prognosis of the disease. Here, we conduct epigenome-wide association studies (EWAS) of these factors and ~3year survival using Illumina Methylation EPIC blood DNA methylation profiles from 409 individuals in the Head and Neck 5000 (HN5000) study. CpG site associations below our multiple-testing threshold (PBonferroni < 0.05) with both a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…For instance, Langdon et al identified a panel of DNA methylation biomarkers for early diagnosis of renal cell carcinoma. Besides, DNA methylation of SPEG located at Chr2:220325443-220326041 could potentially regulate oropharyngeal cancer survival [17]. Shen et al reported that hypermethylation of SSTR2 promoter could be used to predict prognosis of laryngeal squamous cell carcinoma in males [18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Langdon et al identified a panel of DNA methylation biomarkers for early diagnosis of renal cell carcinoma. Besides, DNA methylation of SPEG located at Chr2:220325443-220326041 could potentially regulate oropharyngeal cancer survival [17]. Shen et al reported that hypermethylation of SSTR2 promoter could be used to predict prognosis of laryngeal squamous cell carcinoma in males [18].…”
Section: Introductionmentioning
confidence: 99%